Current topics in developmental biology - Schatten, Gerald; ScienceDirect eBooks (San Diego ; London : Academic Press, 2005)
Current Topics in Developmental Biology provides a comprehensive survey of the major topics in the field of developmental biology. The volumes are valuable to researchers in animal and plant development, as well as to students and professionals who want an introduction to cellular and molecular mechanisms of development. The series has recently passed its 30-year mark, making it the longest-running forum for contemporary issues in developmental biology. This volume contains nine important contributions from leading minds in developmental biology.* Presents major contemporary issues and astonis.
Copyright; table of contents; front matter; Contributors; body; 1. Stepwise Commitment from Embryonic Stem to Hematopoietic and Endothelial Cells; 2. Fibroblast Growth Factor Signaling and the Function and Assembly of Basement Membranes; 3. TGF-Beta Superfamily and Mouse Craniofacial Development: Interplay of Morphogenetic Proteins and Receptor Signaling Controls Normal Formation of the Face; 4. The Colors of Autumn Leaves as Symptoms of Cellular Recycling and Defenses Against Environmental Stresses.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Embryology; Cytogenetics; Cytogenetics; Embryology; Electronic books